Laboratory and dialysis characteristics in hemodialysis patients suffering from chronic itch: results from a representative cross-sectional study - Weisshaar, Elke; Weiß, Melanie; Passlick-Deetjen, Jutta; Tschulena, Ulrich; Maleki, Klaudia; Mettang, Thomas (BMC nephrology, 2015)
A representative cross-sectional study showed that chronic itch (lasting for a minimum of 6 weeks) affects 25.2 % (point prevalence) of hemodialysis (HD) patients. Pathophysiology and etiology of chronic itch (CI) in HD are still unclear.
Gesehen am 30.06.2020